Characterisation of the whole-genome wide hexokinase gene family unravels the functional divergence in pear (Pyrus bretschneideri Rehd.). Issue 3 (4th May 2018) - Yu, Li'ang; Li, Jiaming; Li, Leiting; Huang, Yuhua; Li, Xiaolong; Qiao, Xin; Liu, Xing; Wu, Jun
ABSTRACT: Hexokinase genes (HXK ) encode enzymes that play an important role in fruit quality and plant development because they participate in the first step of the glycolytic pathway for sugar accumulation and metabolism. In this study, the authors conducted analysis of the phylogeny, gene structure, and expression of HXK genes in pear ( Pyrus bretschneideri Rehd.), comparing them with 7 other plant species. A total of 10 HXK protein sequences from pear and 33 HXK s from 7 other species were identified and clustered into 4 groups, matching their motif classification. Duplication events and motif structure variation attributed the diversification of HXK genes, supported by differential expression pattern of PbrHXKs from pear fruit transcriptome data and qRT – PCR verification. Combining pear fruit soluble sugar content data and analyses above, PbrHXK1 and PbrHXK3 were identified as important candidate genes in sorbitol, fructose, and glucose accumulation during pear fruit development. PbrHXK1 and PbrHXK3 were identified as important candidate genes in sorbitol, fructose, and glucose accumulation during pear fruit development. Subsequent research on these highly expressed PbrHXKs will benefit the enhancement of sugar content and quality in pear.